Castor: more than oil - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Observing the results of leaving castor plants to grow on fallow land an increase in soil moisture and organic matter content, and good weed control Julius Mwangwale, an innovative farmer in Tanzania, has experimented successfully with...